Levodopa-based device-aided therapies for the treatment of advanced Parkinson's disease: a social return on investment analysis - Inez Denham; Roxanne Maurin; Irene Deltetto; Anna Stefanie Mikolaizak; Jenny B. Waern; Colman Taylor; Colman Taylor (Frontiers Media S.A., 2024)
IntroductionParkinson's disease (PD) is an incurable, progressive, neurodegenerative disorder. As PD advances and symptoms progress, patients become increasingly dependent on family and carers. Traditional cost-effectiveness analyses (CEA) only consider patient and payer-related outcomes, failing to acknowledge impacts on families, carers, and broader society. This novel Social Return on Investment (SROI) analysis aimed to evaluate the broader impact created by improving access to levodopa (LD) device-aided therapies (DATs) for people living with advanced PD (aPD) in Australia.MethodsA forecast SROI analysis over a three-year time horizon was conducted. People living with aPD and their families were recruited for qualitative interviews or a quantitative survey. Secondary research and clinical trial data was used to supplement the primary research. Outcomes were valued and assessed in a SROI value map in Microsoft Excel™. Financial proxies were assigned to each final outcome based on willingness-to-pay, economic valuation, and replacement value. Treatment cost inputs were sourced from Pharmaceutical Benefits Schedule (PBS) and Medicare Benefits Scheme (MBS) published prices.ResultsTwenty-four interviews were conducted, and 55 survey responses were received. For every $1 invested in access to LD-based DATs in Australia, an estimated $1.79 of social value is created. Over 3 years, it was estimated $277.16 million will be invested and $406.77 million of social return will be created. This value is shared between people living with aPD (27%), their partners (22%), children (36%), and the Australian Government (15%). Most of the value created is social and emotional in nature, including reduced worry, increased connection to family and friends, and increased hope for the future.DiscussionInvestment in LD-based DATs is expected to generate a positive social return. Over 50% of the value is created for the partners and children of people living with aPD. This value would not be captured in traditional CEA. The SROI methodology highlights the importance of investing in aPD treatment, capturing the social value created by improved access to LD-based DATs.